Synthesis and Structural Diversity of Triaryl(phenylethyl)silanes - Linnemannstöns, Marvin; Neumann, Beate; Stammler, Hans-Georg; Mitzel, Norbert W. (Synthesis, 2020)
Starting from trichloro(phenylethyl)silane, six differently fluorinated triaryl(phenylethyl)silanes were synthesized by salt elimination reactions and their structures were determined by X-ray diffraction analysis. Tris(pentafluorophenyl)(phenylethyl)silane reveals a folded structure due to intramolecular π-stacking interactions, while those with a lower degree of fluorination show either intermolecular π-stacking or no interplay between the aryl groups. A similar folded structure was observed for (4-methylphenethyl)tris(pentafluorophenyl)silane and [2-(naphth-2-yl)ethyl]tris(pentafluorophenyl)silane, both generated from the corresponding trichlorosilanes. In contrast, the inversely fluorinated [2-(pentafluorophenyl)ethyl]triphenylsilane only revealed intermolecular π-stacking interactions. Compounds with tetrafluoropyridyl substituents behave differently; with these compounds, π-stacking is only observed between the fluorinated units. All compounds were analyzed by NMR and IR spectroscopy, elemental analyses and single-crystal X-ray diffraction, and found to have strong H/C/N/F···F and N···C contacts.
Keywords: inter/intramolecular π-stacking; solid-state structures; London dispersion; bridged arenes; fluorinated arenes